2020
DOI: 10.7150/jca.41834
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic targets of the nuclear division cycle 80 (NDC80) complexes genes in lung adenocarcinoma

Abstract: Background: Lung cancer is the most common cancer worldwide, both in terms of the incidence and mortality. NDC80 complex comprising of NDC80, NUF2, SPC24, and SPC25 is a heterotetrameric protein complex located in the outer layer of the kinetochore and plays a critical role in mitosis. This study focuses on the effects of NDC80 complex genes on clinical features and prognosis in lung adenocarcinoma (LUAD). Materials and methods: Expression of NDC80 complex in LUAD and related clinical information was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
3
16
1
Order By: Relevance
“…Several hub genes, such as BUB1B, CDC45, BUB1, TTK, TOP2A, MCM2, NDC80, and DTL, have been reported to be associated with poor prognosis in patients with lung adenocarcinoma (Hayama et al, 2006;He et al, 2019;Liu et al, 2017;Perez-Pea et al, 2017;Song et al, 2018;Sun et al, 2020). Our findings corroborate these results.…”
Section: Discussionsupporting
confidence: 90%
“…Several hub genes, such as BUB1B, CDC45, BUB1, TTK, TOP2A, MCM2, NDC80, and DTL, have been reported to be associated with poor prognosis in patients with lung adenocarcinoma (Hayama et al, 2006;He et al, 2019;Liu et al, 2017;Perez-Pea et al, 2017;Song et al, 2018;Sun et al, 2020). Our findings corroborate these results.…”
Section: Discussionsupporting
confidence: 90%
“…KIF20A also has been detected as being overexpressed in numerous types of human malignancies, including LUAD, and its overexpression can stimulate LUAD cells' proliferation [48]. Matching our results, Sun et al [49] also reported that NDC80 expression was strikingly elevated in LUAD and related to prognosis. Interestingly, relevant studies about TPX2, MELK, KIF2C, and KIF11 also have been reported in LUAD, and they are all implicated with the progression and poor prognosis of LUAD [50][51][52][53].…”
Section: Discussionsupporting
confidence: 89%
“…NUF2 is also an oncogene that is over-expressed on several cancers [5,20], including lung adenocarcinoma. Comparing with previous study, the NUF2 expression in multiple databases was signi cantly higher than in normal tissues, and also signi cantly higher in LUAD and LUSC [7].…”
Section: Discussioncontrasting
confidence: 60%
“…The nuclear division cycle 80(NDC80) complex is a heterotetrameric protein complex, and NUF2, as an important part of the NDC80 complex, is essential for kinetochore-microtubule attachment and chromosome separation [3]. Previous evidence demonstrated that NUF2 plays as a prognostic biomarker and therapeutic target in hepatocellular carcinoma, breast cancer and oral cancer [4][5][6], and NDC80 complex gene might be an early indicator of diagnosis and prognosis of lung adenocarcinoma [7]. These studies have shown that NUF2 might be a candidate biomarker and therapeutic target in cancer with great potential, but the role of the NUF2 gene in NSCLC has not been systematically explored in multiple aspects.…”
Section: Introductionmentioning
confidence: 99%